Acupuncture for Internet addiction: A protocol for systematic review. Issue 12 (26th March 2021) - Chen, Yalin; Zhang, Lingrui; Liu, Yan; Yang, Yan; Qiu, Mimi; Wang, Yang; Peng, Wei; Li, Hui; Zhu, Tianmin
Abstract: Background: Internet addiction (IA) has become a global problem characterized by excessive use of the internet, compulsive, and deleterious personal behaviors. Acupuncture has gained more and more attention in the treatment of IA. However, evidence of its effectiveness is lacking. The purpose of this systematic review is to evaluate the efficacy and safety of acupuncture in the treatment of IA. Methods: The following databases will be searched from the inception to September 30, 2020: the Cochrane Library, PubMed, Embase, Web of Science, China National Knowledge Infrastructure, Wan-fang database, Chinese Biomedical Literature Database, and Chinese Scientific Journal Database. The research on acupuncture and IA meets the screening criteria, and two independent reviewers performed citation screening, data extraction, and risk assessment of bias. We used Cochrane Review Manager 5.3 software for statistical analysis. Results: The findings will be published at scientific conferences or in a peer-reviewed journal. This study is based on the existing research, so there is no need for ethical approval. Conclusion: This systematic review provides evidence for the efficacy of acupuncture in treating IA disorder, and it is of great significance for effective clinical routine treatment of IA. Trial registration number: INPLASY 2020120099